KEDUDUKAN KOMISI PENGAWAS PERSAINGAN USAHA DALAM HAL TERJADINYA MERGER - Agustini, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The birth of Act No 5 Year 1999 concerning Prohibition of Monopolistic Practises and Unfair Business deliver its own message to the government to establish regulation regarding mergers as contained in Article 29 Paragraph (3) and Article 29 Paragraph (2). Growing competition between business entities in the market resulted in the business-strategy competing to find new strategies to keep their business running well. One of them with merger. The government set up Government Regulation Number 57 Year 2010 regarding the Merger or Consolidation of Business and Acquisition Agency Shares which may Result in Monopolistic Practices and Unfair Business Competition. With the aim that the implementation of the merger has clear rules and legal certainty in the implementation of the merger. Based on this, the authors want to try to raise issues about how the Commission’s position in the event of a merger and how the implementation of the merger based on Government Regulation Number 57 Year 2010. In writing this thesis, the author uses research methods to the nature of juridical normative in descriptive research, and data obtained from the research literature which is then processed by way of editing ang to analysis with analiysis of qualitative. Techniques of data collection in done by the study of documents. From the result of research conducted in can be concluded that the Commission has a very important position because it was believed by the Government Regulation Number 57 Year 2010 as an institution that became the backbone, enforcement and oversight of merger. As for the implementation of the merger is done by the company’s internal preparation to meet the requirements of the merger, and after they met, then proceed with the impelementation phase of the merger according to Government Regulation Number 57 Year 2010 regarding the plan of merger must be notified to the Commission and Business can also do consulting on a voluntary basis to the Commission.